Hydrogen Peroxide and Hypochlorous Acid Influx Through the Major S. Typhimurium Porin Ompd Is Affected by Substitution of Key Residues of the Channel - Morales-Sierra, E (Academic Press, 2015)
OmpD is the major Salmonella enterica serovar Typhimurium (S. Typhimurium) porin and mediates hydrogen peroxide (H2O2) influx. The results described herein extend this finding to hypochlorous acid (HOCl), another reactive oxygen species that is also part of the oxidative burst generated by the phagosome. S. Typhimurium cells lacking OmpD show decreased HOCl influx, and OmpD-reconstituted proteoliposomes show an increase in the uptake of the toxic compound. To understand this physiologically relevant process, we investigated the role of key OmpD residues in H2O2 and NaOCl transport. Using a theoretical approach, residue K16 was defined as a major contributor to the channel electrostatic properties, and E111 was shown to directly participate in the size-exclusion limit of the channel. Together, we provide theoretical, genetic, and biochemical evidence that OmpD mediates H2O2 and NaOCl uptake, and that key residues of the channel are implicated in this process. © 2015 Elsevier Inc. All rights reserved.